STUNTING PREVENTION THROUGH FIRST 1.000 DAYS OF LIFE (HPK) PROGRAM EDUCATION IN MANUKAN KULON SUB-DISTRICT, TANDES DISTRICT, SURABAYA - Nenccy Mirasari; Vikko Brilian Arifin; Rizky Werdaningtyas; Yustina Dwi Nastiti; Rio Ridho'i; Muchammad Daffa Rozak Perdana; Nida Inva Tassya; Hanindia Aisyah Rosanti; Willa; Lanny Ramli (Universitas Airlangga, 2023)
The stunting prevalence rate in Indonesia in 2022 is still 21.6%, especially in East Java, the stunting prevalence rate still reaches 19.2%. The Surabaya City Government has a target to declare zero stunting by 2023 through the 1000 HPK Movement. One thousand HPK is the period from conception to the age of 24 months which is an important period to improve children's health because if at this time there is a developmental and functional delay in children, it cannot be changed or only partially reversible. Children are stunted if their height for their age is more than two standard deviations below the median WHO child growth standard. Community service activities in the form of education for the 1000 HPK Movement will be held on Saturday, July 22, 2023 at Balai RW 02 Manukan Kulon Village. Community service activities are carried out in the form of nutrition counseling and interactive dialogue between resource persons and participants. The educational activity was attended by pregnant women, breastfeeding mothers, and mothers who have children less than 2 years old with a total of 35 participants. The results of Wilcoxon's test on the Pre-test and post-test filled by participants showed that there was an increase in the knowledge of education participants about the 1000 HPK Movement. This activity is expected to be a provision for participants in preparing healthy children and avoiding stunting.